Meningkatkan Kecerdasan Natural Anak Usia Dini melalui Pengenalan Hewan di TK Pelita Kota Bandung - Yeni Suhartini; Ala Laela (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
The purpose of research is to find out how the activity of early childhood in improving natural intelligence through the introduction of animals in Pelita Kindergarten Bandung and to find out how much improvement of natural intelligence through the introduction of animals. The research problem is how the introduction of animals made to the natural intelligence of early childhood in Pelita Kindergarten Bandung. The research method used is Classroom Action Research method. Subjects in this study were all children early childhood amounting to 26 children. The instruments used are observation guidelines, interviews, and documentation. Data analysis techniques used quantitative descriptive using percentage and qualitative. Data analysis uses data reduction, data model, and conclusion. The results showed that in cycle I, the average value obtained by children Developing Very Good of 17%. While in cycle II, the average result of children Developing Very Good increased to 65%. This shows that by using the introduction of animals, the early child's natural intelligence in Pelita Kindergarten Bandung increased by 48%.